Heidegger's contribution to the understanding of work-based studies - Gibbs, Paul (Professional and practice-based learning, 2011)
This book seeks to develop the philosophy of Heidegger notion and reflects the growing importance of work based studies which is becoming of special interest to higher education institutions and commercial organisations. The author acknowledges the dominance of the economic discourse of higher education, but in this book he tries to argue that Heidegger offers a phenomenological approach to understanding the diversity to higher education that work based learning can bring. The book offers a structured argument for a phenomenological understanding of both the educational institution and the commercial environment to be considered as workplaces.